Impact Research in Human Resources: A Systematic Review - Bernardino , Ana Beatriz; Alves , Ana Sofia; Martins, Andreia Da Costa; Gonçalves , Beatriz; Batista , Beatriz; Malta , Carla; Moreno, Carolina; Santos, Catarina; Pinto, Cristiana; Dzoen , Choi Yi; Ribeiro , Cláudia Sofia; Pinto, Cristiana; et al. (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
This collaborative study, conducted by Master's students in Human Resources (HR), aims to provide valuable insights into the main characteristics of research conducted in the field of Human Resources Management and Development in the year 2022. The study employs a systematic review approach, analysing articles published in the eight highest-impact Human Resources journals according to the Scimago Journal Rank (SJR) as of February 2023. The main inclusion criterion for creating the sample was journals incorporating the term "Human Resources" in their title. The top eight ranked journals were Human Resource Management Review, Human Resource Management, Human Resource Management Journal, Human Resource Development Review, International Journal of Human Resource Management, Research in Personnel and Human Resources Management, Human Resource Development Quarterly, and Human Resource Development International. These journals are published by Elsevier and Wiley-Blackwell. For in-depth analysis, only articles with abstracts available through institutional SCOPUS accounts were considered. This selection process yielded a total of 377 articles, which were meticulously analysed across 4,524 units of context. The findings reveal that a significant majority (88%) of the articles focused on HR organizational studies, while 7% addressed societal HR issues, and 5% concentrated on individual HR issues. Among the most frequently researched topics were organizational HR Development, Leadership and Team Management, Performance Management, Career Management, Organization and Work Design, as well as Diversity and Inclusion Management. In terms of research methods, qualitative studies emerged as the predominant approach in the reviewed articles. Notably, the systematic literature review and inquiries through open-ended questionnaires and interviews were the primary data collection methods employed. Content analysis was the most used method to analyse the data. The studies primarily involved employees as participants, as well as secondary data. Regarding research affiliation, the United States of America exhibited the highest representation, with institutions such as the University of Minnesota, Texas A&M University, and Louisiana State University leading the way. European universities, including Tilburg University and Ghent University, also made notable contributions to the HR research landscape. This systematic review provides a comprehensive analysis of the highest-impact Human Resources journals, shedding light on the current state of research in the field. The identified research topics and methodologies highlight the key areas of investigation and offer valuable guidance for researchers, practitioners, and scholars in HR. The study's findings contribute to the ongoing advancement of HR knowledge and serve as a valuable resource for the HR community at large.